Introducing reticular chemistry into agrochemistry. (25th November 2020) - Sun, Da-Wen; Huang, Lunjie; Pu, Hongbin; Ma, Ji
Abstract : MOFs and COFs open up a new journey for agrochemistry evolution with the magic of reticular chemistry. Abstract : For survival and quality of life, human society has sought more productive, precise, and sustainable agriculture. Agrochemistry, which solves farming issues in a chemical manner, is the core engine that drives the evolution of modern agriculture. To date, agrochemistry has utilized chemical technologies in the form of pesticides, fertilizers, veterinary drugs and various functional materials to meet fundamental demands from human society, while increasing the socio-ecological consequences due to inefficient use. Thus, more useful, precise, and designable scaffolding materials are required to support sustainable agrochemistry. Reticular chemistry, which weaves molecular units into frameworks, has been applied in many fields based on two cutting-edge porous framework materials, namely metal–organic frameworks (MOFs) and covalent-organic frameworks (COFs). With flexibility in composition, structure, and pore chemistry, MOFs and COFs have shown increasing functionalities associated with agrochemistry in the last decade, potentially introducing reticular chemistry as a highly accessible chemical toolbox into agrochemical technologies. In this critical review, we will demonstrate how reticular chemistry shapes the future of agrochemistry in the fields of farm sensing, agro-ecological preservation and reutilization, agrochemical formulations, smart indoor farming, agrobiotechnology, and beyond.